UNSTEADY NATURAL CONVECTION FLOW THROUGH A VERTICAL POROUS CHANNEL FILLED WITH POROUS MATERIALS UNDER THE EFFECT OF THERMAL RADIATION - Bichi, Yusuf A.; Abiodun, O. A. (FUDMA JOURNAL OF SCIENCES, 2023)
The paper examines the velocity and heat transfer on unsteady natural convection flow through a vertical porous channel filled with porous materials under the effect of thermal radiation. The study considered the fluid flow to be through an infinite vertical porous channel filled with porous materials and the energy equation in the flow model is examined using non-linear Rosseland heat diffusion. The partial differential equations associated with the flow formation are transformed into ordinary differential equations (ODEs) using similarity variables and the resulting ODEs are solved by Adomian decomposition method (ADM). Finally, the results are presented on graphs as velocity and temperature profiles for various values of the controlling physical parameters involved in the problem. In the course of investigation, it was found that; the fluid velocity increases with increase in thermal radiation and Darcy number and the fluid temperature was seen to increase with increase in thermal radiation.